2018
DOI: 10.5114/hm.2018.81014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of relationships between different training load monitoring tools in elite U-20 soccer

Abstract: Purpose. the study analysed the responses from different training load monitoring tools in the elite U-20 soccer category and checked the level of association between these responses. Methods. the participants were 10 elite male soccer players (age, 18.61 ± 0.95 years; height, 176.81 ± 5.03 cm; body mass, 70.32 ± 8.41 kg). the progressive test to exhaustion assessed maximum oxygen consumption and maximum heart rate. the athletes were monitored over 15 training sessions with a heart-rate-based method (Edwards) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Heart rate is commonly used to monitor training intensity in elite football. 26 In the present study, the FM elicited greater HR than the 10v10 (set-piece game purpose), 10v10 (free play), 14v14, 7v7 and the 8v8. A systematic review showed that players obtained higher %HR when playing in a smaller format compared to other higher format of SSG´s, 3 however our present findings indicated that no difference comparing the FM with the 4v4 and the 6v6 pre-season training tasks.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Heart rate is commonly used to monitor training intensity in elite football. 26 In the present study, the FM elicited greater HR than the 10v10 (set-piece game purpose), 10v10 (free play), 14v14, 7v7 and the 8v8. A systematic review showed that players obtained higher %HR when playing in a smaller format compared to other higher format of SSG´s, 3 however our present findings indicated that no difference comparing the FM with the 4v4 and the 6v6 pre-season training tasks.…”
Section: Discussionsupporting
confidence: 42%
“…In order to ensure the ecological validity of the data collected, the planning and execution of the training did not suffer interference from the researchers. 26,27 During the study period, the athletes performed 2–3 strength training sessions per week. These sessions took place in the gym under the supervision of the club.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the fact that, in the preseason, players do not play official matches. During this period, the players train daily, and this process is better controlled by the coaching staff, which monitors and adjusts the workloads according to the previously planned periodization 1,2 . In addition, during this period, soccer players participated in base camps, where they are allowed to feed and sleep better, favoring the state of overcompensation 10,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In soccer, the purpose of athletic planning is to appropriately manage the training load to optimize sports performance 1 through a process of planning, monitoring, and load adjustment. Effective training loads are among the key issues for coaches and players 2 . Sports preparation is usually divided into two phases: the preparatory and competitive period.…”
Section: Introductionmentioning
confidence: 99%